Effects of stent design on LDL accumulation at the carotid artery bifurcation - Nasrul Hadi, Johari; Menichini, Claudia; Hamady, Mohamad; Xu, Xiao Y. (Universiti Malaysia Pahang, 2019)
Restenosis typically occurs in regions of low and oscillating wall shear stress which also favours the accumulation of atherogenic macromolecules such as low-density lipoprotein (LDL). This study aims to determine how stent strut design may affect in-stent restenosis at the carotid artery bifurcation following carotid artery stenting (CAS) by means of computational simulation. LDL concentrations were compared for post-stent carotid and the contralateral models reconstructed from patient-specific images. Our results show that closed-cell stent designs are more likely to create atheroprone and procoagulant flow conditions than open-cell designs due to larger area exposed to high LDL concentration.